Canto de sirena de Gregorio Martínez y la estética de la novela posterior al “Boom” - Valenzuela Garcés, Jorge (2018)
n this article, the novel Canto de sirena by peruvian writer Gregorio Martínez (1942-2017) is analyzed based on the aesthetics that nurtured postboom writers. Our purpose is to observe the use of certain assumptions, principles and strategies that were generated for the new novelist in response to the aesthetics of the “boom” and the project of the total novel that became his novelistic ideal. We use the theoretical framework and the ideas put forward by Ángel Rama (1981) and Antonio Skármeta (1984) around the new generation of Latin American narrators.